France’s colonial policy in Algeria (1830-1894 AD) "the religious side as a model" - معيطة ورود; نوفل وضاح (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
This research deals with (France’s colonial policy in Algeria, "the religious aspect as a model") in the period from 1830-1894 AD, which is an important period in the history of Algeria, during which the Algerians suffered a lot from France’s colonial policy, especially with regard to the religious aspect, due to the methods used by France to implement Its religious project, it also examines the factors that helped missionaries achieve their missionary goals, in addition to showing the position of Algerians on this religious policy, and the research concluded that despite the methods that France used to eliminate the Islamic religion, Algerians adhere to their religion, customs and traditions. I fail all of those schemes.